1999
DOI: 10.1597/1545-1569(1999)036<0486:pnmiiw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Nasoalveolar Molding in Infants with Cleft Lip and Palate

Abstract: Presurgical infant orthopedics has been employed since the 1950s as an adjunctive neonatal therapy for the correction of cleft lip and palate. In this paper, we present a paradigm shift from the traditional methods of presurgical infant orthopedics. Some of the problems that the traditional approach failed to address include the deformity of the nasal cartilages in unilateral as well as bilateral clefts of the lip and palate and the deficiency of columella tissue in infants with bilateral clefts. The nasoalveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
241
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(253 citation statements)
references
References 0 publications
5
241
0
7
Order By: Relevance
“…In the group with nasal stents (study group) there was an increased improvement in the columellar length and nasal tip projection as compared to the control group. This was in concurrence with the studies of Maull et al [16], Cutting et al [5] and Grayson et al [10]. We also however found that the improvement of nasal aesthetics was also subject to the compliance of the patients' parents, the tolerance of an individual and even the gauge of the wire used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the group with nasal stents (study group) there was an increased improvement in the columellar length and nasal tip projection as compared to the control group. This was in concurrence with the studies of Maull et al [16], Cutting et al [5] and Grayson et al [10]. We also however found that the improvement of nasal aesthetics was also subject to the compliance of the patients' parents, the tolerance of an individual and even the gauge of the wire used.…”
Section: Discussionsupporting
confidence: 92%
“…Grayson and Maull [8] describe that the principle objective of presurgical nasoalveolar molding (NAM) is to reduce the severity of the initial cleft deformity. Grayson et al [9] described the complete impression technique and NAM appliance fabrication, adjustments and complications of NAM therapy. They stated that the objective of PNAM is to reduce the severity of the original deformity and thereby enable the surgeon to achieve better repair of the alveolus, lip and nose.…”
Section: Discussionmentioning
confidence: 99%
“…Barry Grayson, DDS and Court Cutting, MD, adopted this theory to the nasal cartilages of infants born with cleft lip and palate (3,(6)(7)(8). They have been publishing and sharing their experience of 20 years on presurgical nasoalveolar molding (NAM).…”
Section: Molding Of the Cartilagesmentioning
confidence: 99%
“…Recent prospective studies have clearly shown the questionable benefit of conventional presurgical orthopedics in the unilateral cleft lip and palate patients [10,11]. Presurgical nasoalveolar molding was described in the last decade which conceptualized the combination of nasal cartilage molding along with the conventional form of alveolar orthopedics [7]. However, the critiques of the presurgical treatment have described it as unnecessary, tedious and costly procedure [12].…”
Section: Discussionmentioning
confidence: 99%
“…Grayson [7] conceptualized the combination of the presurgical nasal molding with the conventional form of the presurgical orthopedics. Since 2005, at The Nitte Meenakshi Institute of Craniofacial surgery, PNAM as described by Grayson [7] has been used for the patients with unilateral cleft lip and palate (UCLP). The PNAM requires weekly visits over a period of 3-5 months.…”
mentioning
confidence: 99%